Efektivitas Model Pembelajaran Visualization, Auditory, Kinesthetic terhadap Hasil Belajar Siswa - Verranisa Sevia Nuraini; T Heru Nurgiansah; Supri Hartanto (CV. Rayyan Dwi Bharata, 2024)
This study aims to determine the effectiveness of visualization, auditory, and kinesthetic learning models on the learning outcomes of Civics Education (PPKn) for grade VIII E students at SMP Negeri 3 Kasihan. This research was conducted because the learning outcomes of Civics Education for students are still not optimal. This is caused by several factors, one of which is the use of inappropriate learning models. This study used a quantitative method, a survey research type to determine the effectiveness of visualization, auditory, and kinesthetic learning models on Civics Education learning outcomes. The population in this study consisted of 155 students, while the sample in this study consisted of 32 students. Data collection techniques in this study used questionnaires and test evaluations. The data analysis used were validity test, reliability test, normality test, homogeneity test, simple linear regression test, and hypothesis test using SPSS 22. Based on the results of the study, it is known that the significance value is 0.000, where 0.000 0.05. Meanwhile, the t-value t-table (5.040 1.697). These results indicate that the Visualization, Auditory, and Kinesthetic learning model variables are effective for the Civics Education learning outcomes variable. Thus, this research can be said to be significant and concludes that H0 is rejected and H1 is accepted.